Individual training for farmers based on results from protein and ATP rapid tests and microbiological conventional cultural methods improves hygiene in pig fattening pens - Heinemann, Céline (J Anim Sci, 2019)
Optimal hygiene management is an essential part of maintaining a high standard of health in conventional pig production systems and for the successful interruption of infection chains. Currently, efficiency assessments on cleaning and disinfection are only performed by visual inspection or are neglected completely. The aim of this study was to evaluate the available methods for on farm monitoring of hygiene, identify critical points in pig pens and use the data obtained for training purposes. In addition to visual inspection by assessing the cleanliness, microbiological swab samples, i.e., aerobic total viable count (TVC), total coliform count, methicillin-resistant Staphylococcus aureus (MRSA), and extended-spectrum β-lactamases-producing bacteria (ESBL), swab samples for ATP as well as protein residues and agar contact plates combined with 3 different culture media, were applied and ranked according to their suitability for livestock farming. Samples were collected on at least 15 critical points from one representative pen on 6 pig fattening farms with various hygiene management practices after cleaning and disinfection. After the first sampling, farmers were trained with their individual results, and sampling was repeated 6 mo after training. Nipple drinkers, feeding tubes (external and inner surface), and troughs (external and inner surface) showed the greatest bacterial loads (TVC: 4.5–6.7 log(10) cfu cm(-2)) and values for ATP and protein residues; therefore, these surfaces could be identified as the most important critical points. Spearman rank correlations (P < 0.01) were found between the different assessment methods, especially for the TVC and ATP (r = 0.82, P < 0.001). For rapid assessment on farms, ATP tests represented an accurate and cost-efficient alternative to microbiological techniques. Training improved cleaning performance as indicated by a lower rating for visual inspection, TVC, ATP, MRSA, and ESBL in the second assessment. The monitoring of cleaning efficiency in pig pens followed by training of the staff constitutes a valuable strategy to limit the spread of infectious diseases and antibiotic-resistant bacteria. Special attention should be paid to the sufficient hygiene of drinkers and feeders.